Leadership over a team of musictans in the contest of personally-orienteds studying - L.І. Pankiv (Academy of Cognitive and Natural Sciences, 2006)
The article highlights the requirements to professional acnnties of a music teacher as a leader of a team. The mam principles of pedagogical leadership are considered over musical reaching coUeane from the point of view of personally oriented approach.